Relationship between Teachers' Communication Skills and Students' Academic Well-being with Emphasis on the Mediating Role of Academic Adjustment in Girls' High Schools in Kashmar - javad shalian (مدیریت و چشم انداز آموزش, 2021)
Extended Abstract Abstract The aim of this study was to investigate the relationship between teachers 'communication skills and academic well-being with emphasis on the mediating role of students' academic adjustment. The research method was descriptive-survey. Teachers (143 persons) were selected based on Krejcie and Morgan table by simple random sampling method and 371 students(371 persons)  were selected by cluster random sampling method as a statistical sample. In the present study, the educational welfare questionnaires of Peternin et al. (2014), Baker and Cyriac (1984) academic adjustment questionnaires and communication skills of Queen Dam teachers (2004) were used. Their validity was confirmed by academic experts and their reliability by means of Cronbach's alpha coefficient test was obtained 0.76, 0.89 and 0.72, respectively, and approved. In order to analyze the data, structural equation technique was applied using Lisrel statistical software and Spss26 statistical software. Quantitative results obtained from hypothesis testing of the study showed that there is a positive and significant relationship between teachers 'communication skills and students' academic adjustment and academic well-being. There is a positive and significant relationship between students 'academic adjustment and their academic well-being, and academic adjustment in the relationship between teachers' communication skills and Students' academic well-being has played a mediating role. Introduction Today, education, specifically or generally. is an important part of every person's life, in addition, the quality and quantity of this education also plays an important role in the individual's future life. Therefore, for nearly a century, psychologists have been widely involved in Attempts to identify predictor factors of the academic achievement. Awareness of students' psychological aspects can act as a powerful teaching aid tool. For example, understanding how students behave in certain situations can lead to an increase the effectiveness of educational tools as well as teacher's teaching methods and the education system and ultimately the progress of students (hamedinasab and asgari, 2020). Academic well-being is one of the most important and influential variables on academic performance. It is derived from the basis of positive psychological theory, and those who possess dejected behavior and negative excitements such as anger, disturbance and sorrow; more than others are subject to education drop and drop-out.(Jahani and etal, 2018). Teachers are the most important variable in students' learning. In other words, the most important factor in the educational system is not the teaching materials or teaching methods, but the teachers themselves; and due to this importance, over the years, researchers have examined the internal and external factors effective on the performance of teachers and therefore the performance of students (Teymoriyan and etal, 2018). Communication skills Refers to behaviors through which a person can communicate with others in a way that leads to positive responses and avoid negative ones (Nakagawa and etal, 2019). Given the importance of communication skills and educational adaptation in improving the academic well-being of students, recognizing its affective factors is one of the main necessities of our country's educational system. Therefore, because the researches concern with the above-mentioned variables and their effective amount on the student's educational well-being have not much fulfilled, in the present study, the researcher decided to address the relationship between these variables in the girls' high schools in Kashmar. Therefore, this study examines the question of whether there is a significant relationship between teachers' communication skills and students' academic well-being by emphasizing the mediating role of academic adjustment in girls' high schools in Kashmar. Case study In this study, all teachers and students of girls' secondary schools in Kashmar city have been studied as a case study. Theoretical framework Ardalan and Hosseinchari in a study showed that communication skills can predict students' academic adjustment (Ardalan and Hosseinchari, 2010). Research results have shown that there is a direct relationship between communication skills variables with students' academic well-being and self-efficacy. Accordingly, with increasing and developing teachers' communication skills, students' well-being and self-efficacy will improve (Baezat and Rahimi, 2015). Another study on academic adjustment showed that there is a positive relationship between communication skills and academic adjustment and motivation (Bahadori Khosroshahi and Habibi Kelibar, 2017). Another study has shown that teachers 'communication skills can develop students' self-efficacy and ultimately their academic well-being (Baezat and Rahimi, 2015). Research has shown that friendly and effective communication in the classroom has an effective role in improving the academic atmosphere and academic adjustment of students. Accordingly, academic adjustment will improve academic conditions and lead to high academic performance (Cheong and etal, 2019). Methodology This research is of descriptive-survey type. The study population includes teachers and students of girls' secondary schools in Kashmar. Based on this, 143 teachers were selected by simple random sampling and 371 students were selected by combined cluster random sampling as the sample size. Piternin et al.'s (2014) Academic Welfare Questionnaire, Queen Dam's Teachers' Communication Skills (2004) and Baker's and Cyriac's (1984) Academic Adjustment Questionnaires were used for data collection. Discussion and Results The first hypothesis of the research is to measure the relationship between teachers' communication skills and students' academic adjustment. The strength of the relationship between communication skills and academic adjustment is calculated to be equal to (0.62), which indicates a favorable correlation. The t-test of the test was obtained (7.60), which is greater than the critical value of t at the level of error of 5% (1.96) and shows that the strength of the observed relationship is significant. Therefore, it can be said that there is a positive and significant relationship between teachers' communication skills and students' academic adjustment. The second hypothesis of the research has investigated the relationship between students' academic adjustment and their academic well-being. The strength of the relationship between academic adjustment and academic well-being has been calculated equal to (0.68), which indicates a favorable correlation. The t-test of the test was obtained (7.66), which is more than the critical value of t in the error level of 5% (1.96) and shows that the strength of the observed relationship is significant. Therefore, it can be said that there is a positive and significant relationship between students' academic adjustment and their academic well-being. The third hypothesis of the study analyzed the relationship between teachers' communication skills and students' academic well-being. The strength of the relationship between communication skills and academic well-being has been calculated equal to (0.39), which indicates a favorable correlation. The t-test of the test was obtained (4.37), which is more than the critical value of t at the level of 5% error (1.96) and shows that the strength of the observed relationship is significant. Therefore, it can be said that there is a positive and significant relationship between teachers' communication skills and students' academic well-being. The fourth hypothesis of the study examines the relationship between teachers' communication skills and students' academic well-being with the mediating role of academic adjustment. In order to examine the meditative effect of the academic adjustment in the hypothesis under discussion, the direct effect of the two structures in comparison with the indirect effect when the academic adjustment variable interferes should be examined so that if the effect increases, the mediating effect of the link with the school can be considered acceptable. In the present hypothesis, the power of the direct relationship between communication skills and academic well-being is (0.39). The indirect effect if there is a mediating variable of academic adjustment is:  (0.42) = (0.68) * (0.62) Due to the lower effect of direct path than indirect paths, therefore, the existence of the mediator variable of academic adjustment increases the strength of the relationship and the mediating role of academic adjustment in the present hypothesis is confirmed. Conclusion The results of the first hypothesis of the research showed that there is a positive and significant relationship between teachers' communication skills and students' academic adjustment. This hypothesis is explained by the fact that students try to give more explanations to those of their classmates who are less absorbant and have difficulty in understanding the curriculum, and help them understand class topics (Yazdani and Soleimanpouromran, 2018). These results are consistent with and supported by research findings (Nakagawa and etal, 2019; Alizadeh and Jouybari, 2016; nasri and etal, 2017). Based on this, the first hypothesis of the research is confirmed. The results of the second hypothesis of the study showed that there is a positive and significant relationship between students' academic adjustment and their academic well-being. In explaining this hypothesis, it can be said that a positive attitude intensifies the desire to continue communication and learning (Badri and etal, 2019). With high ability to distinguish emotions and improve mood in students it is exceptable that their academic engagement status will lead to a successful and evolved identity (Oinas and etal, 2021). These results are consistent and supported by the research findings (Razavi Alavi and etal, 2018, Nasri zadeh and Nargesian, 2019, Nair and etal, 2021). Based on this, the second hypothesis of the research is confirmed. The results of the third hypothesis of the study showed that there is a positive and significant relationship between teachers 'communication skills and students' academic well-being.This hypothesis is explained by the fact that improving the learning conditions in the classroom causes Students can be satisfied with the effective teaching in the classroom and look forward to the educational content (Lebares and etal, 2021).  These results are consistent with and supported by research findings (Behroozi and etal, 2018, Hoferichter and etal, 2021). Based on this, the third hypothesis of the research is confirmed. The results of the fourth hypothesis of the study showed that there is a significant relationship between teachers' communication skills and students' academic well-being with the mediating role of academic adjustment. This hypothesis is explained by the fact that students who take the initiative to learn, in comparison with the students who passively attend in class and receive instruction, learn more and better (Ghomi and etal, 2017). These results are consistent with and supported by research findings (Razavi alavi and etal, 2018, Delgado and etal, 2018). Based on this, the fourth hypothesis of the research is confirmed.